Mask wars: China's exports of medical goods in times of COVID-19 - Andreas Fuchs; Lennart Kaplan; Krisztina Kis-Katos; Sebastian S. Schmidt; Felix Turbanisch; Feicheng Wang (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
The COVID-19 outbreak has cut China's supply of and raised the world's demand for face masks, disinfectants, ventilators, and other critical medical goods. This article studies the economic and political factors that are associated with China's exports of medical equipment during the first two months of the global pandemic. Regression results show that-controlled for demand factors-countries with stronger past economic ties with China import more critical medical goods from China at both the national level and the level of Chinese provinces. Friendly political relations, such as the twinning of provinces, appear to work as a substitute for pre-existing economic ties at the provincial level. These findings imply that, to secure access to medical equipment in crises, countries are well advised to either diversify their sources or to develop closer relations with Beijing and China's provinces.
Keywords: F14; F59; H12; H77; H84; P33; 330; COVID-19; crisis management; medical equipment; face masks; strategic exports; disaster aid